Suppression of Mixed Noise in the Similar Images by Using Adaptive LMS L-filters - Kocur, D.; Hudec, R.; Marchevsky, S. (Radioengineering Society, 2000)
In this paper, several adaptive least mean squares (LMS) location-invariant filter (L-filter) modifications will be described. These filters are based on linear combination of order statistics. The adaptive L-filters are able to adapt well to variety of noise probability distribution, including impulsive noise. They also perform well in the case of nonstationary signals and, therefore, they are suitable for image processing, too. Following this L-filter property, applications of the adaptive LMS L-filters for filtering two-dimensional static images degraded by mixed noise consisting of additive Gaussian white noise and impulsive noise will be presented in this paper. Based on conveniently selected experiments intent on image filtering, the properties of a several adaptive L-filters modifications will be demonstrated and compared. It will follow from experiment results, that the L-filter modification called signal-dependent LMS L-filter yields the best results.
Keywords: Non-linear filters; adaptive filters; L-filters; LMS algorithm; image filtering